The Interpretation of Historical Facts: The Study of Historical Writing in the Perspective of Exposition Paragraph - M. Ma'ruf Misbah (Insaniyat : Journal of Islam and Humanities, 2018)
This article discusses the existence of a trend of historical facts interpretation in producing exposition paragraph in historical writing.The objective of this study is to identify historical writing variation in the form of exposition paragraph through interpretation of historical facts.This study uses a historiographic and library research method in the field of linguistics and history. The results show that historical paragraphs can be written in variesforms; it could be in form of narration, historical paragraphs, and in form of exposition that related to the writing form of history. The paragraph of history can be written by keeping the existence of the analytical element in them according to the reasoning ability of its writers. The explanation about history in the form of writing by interpreting historical facts has resulted in an exposition paragraph. This is related to the method of historical writing that should be used as a guide in the writing of history. With an exposition form, historical paragraphs can explain events of history according to the topic of the text. The impact from the existence of that thing is the occurrence of the writing of historical paragraphs not just in one type of paragraph. There is a paragraph of history in the form of a narrative. There are also historical paragraphs in the form of exposition. Thus, bothhave contributed to the development of the writing of history.